Establishment and Maintenance of the Human Naïve CD4+ T-Cell Compartment - Silva, Susana L.; Sousa, Ana E. (Frontiers in Pediatrics, 2016)
The naïve CD4+ T-cell compartment is considered essential to guarantee immune competence throughout life. Its replenishment with naïve cells with broad diverse receptor repertoire, albeit with reduced self-reactivity, is ensured by the thymus. Nevertheless, cumulative data support a major requirement of post-thymic proliferation both for the establishment of the human peripheral naïve compartment during the accelerated somatic growth of childhood, as well as for its life-long maintenance. Additionally, a dynamic equilibrium is operating at the cell level to fine-tune the T-cell receptor threshold to activation and survival cues, in order to counteract the continuous naïve cell loss by death or conversion into memory/effector cells. The main players in these processes are low affinity self-peptide/MHC and cytokines, particularly IL-7. Moreover, although naïve CD4+ T-cells are usually seen as a homogeneous population regarding stage of maturation and cell differentiation, increasing evidence points to a variety of phenotypic and functional subsets with distinct homeostatic requirements. The paradigm of cells committed to a distinct lineage in the thymus are the naïve regulatory T-cells, but other functional subpopulations have been identified based on their time-span after thymic egress, phenotypic markers, such as CD31, or cytokine production, namely IL-8. Understanding the regulation of these processes is of utmost importance to promote immune reconstitution in several clinical settings, namely transplantation, persistent infections and aging. In this mini review we provide an overview of the mechanisms underlying human naïve CD4+ T-cell homeostasis, combining clinical data, experimental studies and modeling approaches.